A case of mediastinal lymphangioma: endosonographic appearance - CEYHAN, BERRİN; BATIREL, HASAN FEVZİ; YÜKSEL, MUSTAFA; KARAKURT, SAİT; BOZKURT, SÜHEYLA (SPRINGER TOKYO, 2011)
Mediastinal lymphangioma is a rare, benign disease characterized by an abnormal proliferation of lymphatic vessels. Although a definitive diagnosis can be best made by surgical resection, computed tomography (CT) and magnetic resonance imaging (MRI) can be used as radiological methods to diagnose a pulmonary lymphangioma preoperatively. Endoscopic ultrasonography is a new method for visualizing pathological changes in the mediastum and may be used for preoperative diagnosis of a pulmonary lymphangioma, which is a rare example of a mediastinal disease.
Keywords: Mediastinal lymphangioma; Endoscopic ultrasonography; CT; ADULTS